Pemberdayaan ibu balita melalui program edukasi tumbuh kembang dan pola asuh anak usia dini di wilayah kerja Puskesmas Bilokka - Pratiwi, Wilda Rezki; Hasriani, Sitti; Asnuddin, Asnuddin; Meisyaroh, Meriem; Nisa, Rahmi Fitriani Karimatun (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Introduction: Preliminary data from the Bilokka Community Health Center indicates that there are still toddlers with developmental disorders due to inappropriate parenting practices, particularly in nutrition, discipline, and communication. This condition risks hindering children's readiness to enter primary education and impacting the quality of future generations. Local surveys revealed that most mothers lack adequate knowledge regarding motor, cognitive, and socio-emotional stimulation of children. Purpose: To educate mothers of toddlers about the importance of monitoring early childhood growth and development and supporting factors such as parenting, nutrition, stimulation, and environmental health. Methods: This Community Service activity was conducted on August 4, 2025, at the Integrated Health Post (Posyandu) in Bilokka Village, Panca Lautang District, targeting 45 mothers of toddlers. The activity was implemented using a participatory approach through direct counseling, group discussions, child stimulation simulation practice, training on the use of the Pre-Screening Development Questionnaire (KPSP), and mentoring through online communication media. Results: 38 of the 45 participating mothers reported gaining a new understanding of child growth and development through this program. Six toddlers at risk of malnutrition were identified and referred to advanced health services. The active involvement of participants in all stages of the program significantly contributed to the program's success. Conclusion: Empowering mothers of toddlers through participatory-based education has proven effective in increasing mothers' knowledge and involvement in early childhood stimulation, which is essential for optimizing child growth and development. Suggestion: Increased collaboration with community health centers (Puskesmas) and Posyandu (Integrated Service Post) cadres is needed by actively involving health workers and Posyandu cadres in participatory educational activities to increase mothers' understanding and involvement in ongoing programs on a regular basis. Keywords: Education; Growth and development; Parenting; Toddler Pendahuluan: Data awal dari Puskesmas Bilokka menunjukkan masih adanya balita dengan gangguan tumbuh kembang akibat praktik pengasuhan yang kurang tepat, terutama dalam aspek nutrisi, disiplin, dan komunikasi. Kondisi ini berisiko menghambat kesiapan anak memasuki pendidikan dasar serta berdampak pada kualitas generasi mendatang. Survei lokal mengungkapkan bahwa sebagian besar ibu belum memiliki pengetahuan memadai mengenai stimulasi motorik, kognitif, dan sosial-emosional anak. Tujuan: Mengedukasi ibu balita tentang pentingnya pemantauan tumbuh kembang anak usia dini serta faktor-faktor pendukung seperti pola asuh, gizi, stimulasi, dan kesehatan lingkungan. Metode: Kegiatan Pengabdian Masyarakat ini dilakukan pada tanggal 4 Agustus 2025 di Posyandu Kelurahan Bilokka Kecamatan Panca Lautang dengan jumlah sasaran sebanyak 45 ibu balita. Kegiatan dilaksanakan dengan pendekatan partisipatif melalui penyuluhan langsung, diskusi kelompok, praktik simulasi stimulasi anak, pelatihan penggunaan Kuesioner Pra Skrining Perkembangan (KPSP), serta pendampingan melalui media komunikasi daring. Hasil: Sebanyak 38 dari 45 ibu peserta mengaku baru memperoleh pemahaman tentang tumbuh kembang anak melalui program ini. Ditemukan enam balita dengan risiko gizi kurang yang telah dirujuk ke layanan kesehatan lanjutan. Keterlibatan aktif peserta dalam seluruh tahapan kegiatan berkontribusi signifikan terhadap keberhasilan program. Simpulan: Pemberdayaan ibu balita melalui edukasi berbasis partisipatif terbukti efektif dalam meningkatkan pengetahuan dan keterlibatan ibu dalam stimulasi dini, yang esensial bagi optimalisasi tumbuh kembang anak. Saran: Perlunya peningkatan kolaborasi dengan Puskesmas dan kader Posyandu dengan melibatkan tenaga kesehatan dan kader Posyandu secara aktif dalam kegiatan edukasi yang partisipatif untuk meningkatkan pemahaman dan keterlibatan ibu dalam program berkelanjutan secara berkala.